Koinōnia in the Symposium: from community to communion? - Lenner, Zdenek (2022)
Plato’s Symposium stages a playful subversion of paiderastia by philosophia through successive interconnected speeches. Phaedrus and Agathon praise Erōs as a god presiding over homoerotic relationships, be it at war or at peace. Pausanias and Eryximachus distinguish between two Erōtes, being eager to supervise these paiderastic communities or even the cosmic harmony. But Aristophanes subverts their perspective by introducing the Androgyne, a combination of male and female, which being displayed by Socrates-Diotima will finally give birth to the Erōs-Daimōn. Only he ensures us real human community by enabling true communion with the divine, witness Alcibiades’ final praise of Socrates.